1997
DOI: 10.1172/jci119721
|View full text |Cite
|
Sign up to set email alerts
|

A p47-phox pseudogene carries the most common mutation causing p47-phox- deficient chronic granulomatous disease.

Abstract: The predominant genetic defect causing p47-phox -deficient chronic granulomatous disease (A47 Њ CGD) is a GT deletion ( ⌬ GT) at the beginning of exon 2. No explanation exists to account for the high incidence of this single mutation causing a rare disease in an unrelated, racially diverse population. In each of 34 consecutive unrelated normal individuals, both the normal and mutant ⌬ GT sequences were present in genomic DNA, suggesting that a p47-phox related sequence carrying ⌬ GT exists in the normal popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
2
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 55 publications
2
93
2
6
Order By: Relevance
“…However, the vast majority of patients with p47phox deficiency carry the homozygous 2-bp deletion in the NCF1 gene, which was also detected in our patients. This mutation results from recombination events between the wild-type gene and the pseudogene [22,23]. Patients with this mutation have been reported to exhibit undetectable levels of p47phox protein expression [23], which was consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…However, the vast majority of patients with p47phox deficiency carry the homozygous 2-bp deletion in the NCF1 gene, which was also detected in our patients. This mutation results from recombination events between the wild-type gene and the pseudogene [22,23]. Patients with this mutation have been reported to exhibit undetectable levels of p47phox protein expression [23], which was consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…These authors suggested that recombination between the wild type p47 phox gene and its pseudogene is the main cause of the autosomal recessive form of chronic granulomatous disease associated with absence of p47 phox protein. The intron-exon structures of the wild type and pseudogene are identical, they are similarly transcribed and there are no major differences in their proximal promoter regions (68). Our new data are compatible with this observation.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, Gorlach et al (68) reported a p47 phox pseudogene that is highly homologous to the gene itself, with the notable exception of a GT deletion at the beginning of exon 2 leading to a frameshift and premature stop codon. These authors suggested that recombination between the wild type p47 phox gene and its pseudogene is the main cause of the autosomal recessive form of chronic granulomatous disease associated with absence of p47 phox protein.…”
Section: Discussionmentioning
confidence: 99%
“…The centromeric and the telomeric part contain gene copies of NCF1, which are expressed as truncated proteins with a very short open reading frame (ORF). Homozygous or compound-heterozygous mutations of this gene cause one form of chronic granulomatous disease, a rare disorder with multi-organ manifestation due to an immunodeficiency [89,134,135]. Recent findings suggest a contribution of NCF1 to the development of hypertension.…”
Section: Genomic Region Of Block Bmentioning
confidence: 99%